Factors affecting farmers' access to Kredit Usaha Rakyat (KUR) in Burno Village, Senduro Subdistrict, Lumajang Regency - Wahyu Windari; Bryan Nugraha Widhigdo; Sunarto; Ugik Romadi (Fakultas Pertanian Universitas Yudharta Pasuruan, 2024)
Introduction: This research aims to describe the factors that influence livestock farmers in accessing Kredit Usaha Rakyat (KUR) in Burno Village, Senduro Subdistrict, Lumajang Regency. Methods: The research method uses a descriptive quantitative approach, determining the sample of respondents using simple random sampling and the Slovin formula for as many as 51 people. Data analysis uses multiple linear regression analysis to measure the influence of internal factors (age, education level, income, length of farming, number of livestock, and cosmopolitan level) and external factors (socio-cultural values, family involvement, role of community leaders, role of breeder organizations, and access to experts) on the capacity of dairy farmers in accessing KUR. Results: The research results show that the variables income, length of farming, cosmopolitan level, and the role of community leaders have a significant effect on the capacity of breeders. Conclusion: The capacity of dairy farmers to access KUR is categorized as moderate and the capacity of dairy farmers is influenced by income, length of farming, cosmopolitan level, and the role of community leaders.